(NiSTORIQ STRANY aLUANK (B:s ((Ns DREWNEJ[IH WREMEN PO (BVIII (NWEK(B) /s - (NsWAZQN(B, (Ng(B. (Ns(B.s; (Nnan ras (NiNSTITUT ISTORIIs ((NeREWAN (B:s (NiN(B-(NT IST(B. (Nnan ra(B,s, 2009)
(NiST(B.-(NKRIT(B. (NISSLEDOWANIE(B, (NIZLOVENNOE NA OSNOWE MATERIALXNYH I PISXMENNYH PERWOISTO^NIKOW (B((NGREKO(B-(NRIMSKIH(B, (NARM(B., (NGRUZ(B., (NWIZANT(B., (NSIRIJSKIH(B, (NARAB(B.), (NA TAKVE OPUBLIKOWANNOJ LIT(B-(NRY(B. (NwPERWYE W ARM(B. (NISTORIOGRAFII IZU^AETSQ IST(B. (NSTRANY aLUANK PERWOBYTNOOB](B., (NRABOWLAD(B. (NI RANNEFEOD(B. (NPERIODOW(B.s
(NuKAZ(B. (NIMEN(B: (NS(B. 330-339s
(NuKAZ(B. (NGEOGRAF(B. (NNAZW(B.: (NS(B.340-346.s
(NbIBLIOGR(B. (NW PODSTRO^(B. (NPRIME^(B. (NI NA S(B.: 330-346.s
Keywords: (NiSTORIQs -- (NaLUANKs